Karakteristik Geomorfologi Daerah Ayuhulalo Dan Sekitarnya Kecamatan Tilamuta, Kabupaten Boalemo - Mamonto, Fajri Kurniawan; Arifin, Yayu Indriati; Akase, Noviar; Manyoe, Intan Noviantari (Journal of Applied Geoscience and Engineering, 2024)
The research was conducted in Ayuhulalo area, which is located in the western part of Gorontalo Province, precisely in Tilamuta Sub-district, Boalemo Regency. The geomorphology of the research area is dominated by hilly to mountainous areas. The purpose of this study is to determine the characteristics of the landscape in the study area, determine Geomorphological units, and identify the type of constituent lithology in each Geomorphological unit with a remote sensing analysis approach based on DEM (Digital Elevation Model) SRTM (Shuttle Radar Topography Mission) data and field observations to identify the lithological conditions of the study area. The method includes aspects of geomorphology such as morphography, morphometry, and morphogenetics. The geomorphology of the study area consists of lava flow hills unit with porphyry andesite and porphyry dacite as the constituent lithology and pyroclastic flow hills unit where volcanic breccia is the constituent lithology.